GORK Channel: A Master Switch of Plant Metabolism?. (May 2020) - Adem, Getnet D.; Chen, Guang; Shabala, Lana; Chen, Zhong-Hua; Shabala, Sergey
Abstract : Potassium regulates a plethora of metabolic and developmental response in plants, and upon exposure to biotic and abiotic stresses a substantial K + loss occurs from plant cells. The outward-rectifying potassium efflux GORK channels are central to this stress-induced K + loss from the cytosol. In the mammalian systems, signaling molecules such as gamma-aminobutyric acid, G-proteins, ATP, inositol, and protein phosphatases were shown to operate as ligands controlling many K + efflux channels. Here we present the evidence that the same molecules may also regulate GORK channels in plants. This mechanism enables operation of the GORK channels as a master switch of the cell metabolism, thus adjusting intracellular K + homeostasis to altered environmental conditions, to maximize plant adaptive potential. Highlights: GORK channels possess the binding motifs and domains that may enable them to operate as ligand-gated channels. Activity of GORK channels may be modulated by cyclic nucleotides, gamma-aminobutyric acid, G-proteins, protein phosphatases, inositol, and ATP. As all aforesaid molecules are known to operate upstream of plant signaling pathways mediating their adaptation to abiotic stresses, GORK channel may therefore operate as a 'master switch' of the cell metabolism, inhibiting energy-consuming anabolic reactions and saving energy for adaptation and repair. This function of the GORK channel may give species a competitive advantage under energy-limiting conditions imposed by environmental stresses and explain a reported increase in GORK transcript levels under abiotic stress conditions.